Brand Communication through Logos in the F&B Industry: A Case Study of Lakeside Fit+ Using Peirce’s Triadic Model - Rahmat Panji Wirayudha; Riksa Belasunda; Ira Wirasari (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
This study explores the strategic deployment of visual elements in the Lakeside Fit+ logo using Peirce's Triadic Model within the competitive food and beverage (F&B) industry. By analyzing how symbols, icons, and indexes such as leaf and fruit illustrations, the cup and straw, hand holding and emphatically pointing, black color, and the typographies, communicate health, freshness, and accessibility, the research elucidates the logo's effectiveness in connecting with health-conscious consumers. The methodology leveraged qualitative visual content analysis to decode these elements, offering insights into how they align with the brand's identity and consumer perceptions. The findings reveal that each component of the logo synergistically reinforces Lakeside Fit+'s commitment to quality and wellness, resonating well with the target audience. Future research is recommended to expand this analysis by comparing the visual branding strategies of other competitors. This research not only contributes to semiotic studies in marketing but also provides actionable insights for enhancing corporate brand communication in the F&B sector.